2009
DOI: 10.1007/s00442-008-1269-6
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of seed arrival and environmental conditions on tropical seedling community structure

Abstract: Though it is recognized that both stochastic and deterministic processes structure all communities, empirical assessments of their relative importance are rare, particularly within any single community. In this paper, we quantify the dynamic effects of dispersal assembly and niche assembly on the seedling layer in a diverse neotropical rain forest. The two theories make divergent predictions regarding the roles of seed arrival and environmental heterogeneity in generating community structure. Put simply, dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 59 publications
4
38
0
Order By: Relevance
“…PAINE; HARMS, 2009;HIGUCHI et al, 2015). According to Higuchi et al (2015), the natural regeneration process in a forest's understory starts with the arrival and subsequent germination of seeds on the forest floor, which, according to Guarigata and Pinard (1998), occurs in an irregular way.…”
Section: Discussionmentioning
confidence: 99%
“…PAINE; HARMS, 2009;HIGUCHI et al, 2015). According to Higuchi et al (2015), the natural regeneration process in a forest's understory starts with the arrival and subsequent germination of seeds on the forest floor, which, according to Guarigata and Pinard (1998), occurs in an irregular way.…”
Section: Discussionmentioning
confidence: 99%
“…Seedling and sapling studies have argued for the importance of negative density dependence (Harms et al 2000;Metz et al 2010), abiotic filtering , or stochastic survivorship (Paine and Harms 2009). However, it is more likely that all of these factors act at the same time (e.g., Swenson and Enquist 2009), making it important to disentangle their importance in structuring tropical tree communities through space and time.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many temporally static investigations of seedling assemblages (Augspurger 1984;Nicotra 1999;Norden et al 2007;Paine et al 2012) and some dynamic investiga-tions of the seedling-to-sapling transition Green et al 2014), but there are few detailed forest-wide investigations of perhaps the largest demographic bottleneck of all: the seed-to-seedling transition (Harms et al 2000;Norden et al 2009;Paine and Harms 2009;Muscarella et al 2013). One of the best known of these investigations comes from Harms et al (2000), who found that the seed-to-seedling transition in a Panamanian tropical forest assemblage was strongly influenced by negative density dependence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, high seed limitation is an ''equalizing'' mechanism that may promote species coexistence by allowing species to avoid hierarchical interspecific competition (i.e., ''winning-by-forfeit''; Hurtt and Pacala 1995). Alternatively, high establishment limitation reflects niche differentiation and habitat specificity which are ''stabilizing'' mechanisms for species coexistence (Tilman 1994, Chesson 2000, MullerLandau et al 2002, Gravel et al 2006, Adler et al 2007, Paine and Harms 2009, Mutshinda and O'Hara 2011.…”
Section: Introductionmentioning
confidence: 99%